PENGARUH MOTIVASI DAN KEMAJUAN TEKNOLOGI INFORMASI TERHADAP MINAT INVESTASI SAHAM - Atika, Sabrina; Nilwan, Arizal (Universitas Merdeka Pasuruan, 2022)
AbstractInvestment is one of the indicators of economic support needed by a nation to improve the welfare of Indonesian citizens. believes that it can add improvement as a lever to drive the economic development of a nation. In macroeconomics, investment also plays a role as a component of national income, gross domestic product (GDP). This research is intended to provide empirical evidence on the effect of motivation and advances in information technology on investment interest. In this study, two independent variables were tested, motivation and advances in gossip technology. The population in this survey was found at the Bandar Lampung Student University. The number of respondents in this study found 50 students. Multiple linear regression was used as the analytical method. As a result, the research shows that motivation has a positive effect on student investment interest and technological progress does not positively affect student investment interest.